Variasi Metode Guru dalam Penguatan Ayat dan Hadis pada Mata Pelajaran Al-Qur’an Hadis di Madrasah Aliyah Negeri Tanjungbalai - Yani, Salwa Saphija (Medan Resource Center, 2024)
The purpose of this study was to explain the methods used in strengthening verses and hadiths in the Al-Qur'an Hadith subject at the Tanjungbalai State Islamic Senior High School. In addition, it describes how to apply variations in methods in strengthening verses and hadiths in the Al-Qur'an Hadith subject, and wants to know the supporting and inhibiting factors in applying variations in teacher methods in strengthening verses and hadiths. This study uses a qualitative-descriptive research method. So that the results obtained show that the methods used in strengthening verses and hadiths in the Al-Qur'an Hadith subject are the lecture method, the lecture method plus picture and picture question and answer method, the discussion method, the demonstration method plus tailren method, the drill/exercise or memorization method, and the assignment method. While the teacher's method in applying the method in strengthening verses and hadiths is quite good when seen from the teacher first understanding the learning material, learning objectives, student characteristics, choosing the right method, applying several methods, and paying attention to student responses and providing evaluations/assessments. The supporting and inhibiting factors include the ability of educators, teacher factors, students, and media and completeness of the library. Meanwhile, the inhibiting factors are a lack of understanding of student characteristics and a lack of learning media facilities.